POTENSI SAMPAH SEBAGAI BAHAN BAKU PUPUK ORGANIK - Hermawan Budiyanto; Sriyanto Sriyanto (JURNAL LITBANG PROVINSI JAWA TENGAH, 2011)
Population growth needs to be matched increase in agricultural production, to avoid food crisis. Increased production pursued through intensification, with inorganic fertilizer. In the "Bali Ndeso Mbangun Desa" that: The use of inorganic fertilizers have an impact in declining soil fertility, availability is often not sufficient, so that should be substituted with organic fertilizer. "Go Organic", to "go-organic farming the land." Organic fertilizers can be made from agricultural waste or garbage. The availability of potential waste to be processed into organic fertilizer, continuity in tune with the population and economic activity. Obstruction: there is no waste sorting organic and non organic waste. The quality of organic fertilizer from garbage Traditional Markets meet the required standards of the Ministry of agriculture, organic fertilizer from household waste, material element of follow-up (gravels, glass, plastic) on top of provisions. Organic fertilizer from solid waste landfill (Final Disposal), many elements that have not been in accordance with the provisions of : C / N ratio of 29.47 above the value required (10-25); Materials follow-up of 2.77% above that required ( maximum 2%), Heavy Metal, Pb (58.17 ppm) and Cd (18.36 ppm), which should each below 50 ppm and below 10 ppm, Zn micro elements as much as much as 0.760% and 0.401% Fe still above provisions (a maximum of 0.500% and 0.400%). His role on the fertilizer requirement of 11.04 to 18.05% in Jepara, Klaten 29.51 to 30.70% and in Temanggung 34.03 to 38.76%.